2021
DOI: 10.3892/ijmm.2021.4860
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous spermine attenuates diabetic kidney injury in rats by inhibiting AMPK/mTOR signaling pathway

Abstract: diabetic nephropathy (dN) is the primary cause of end-stage renal disease, which is closely associated with dysfunction of the podocytes, the main component of the glomerular filtration membrane; however, the exact underlying mechanism is unknown. Polyamines, including spermine, spermidine and putrescine, have antioxidant and anti-aging properties that are involved in the progression of numerous diseases, but their role in dN has not yet been reported. The present study aimed to explore the role of polyamines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…As predicted, db/db mice showed a higher mRNA expression of SAT1 in both the renal cortex and medulla, and also a stronger level of SAT1 expression in situ compared with db/m mice. These findings suggest a potential role of SAT1 in the development of type 2 DKD, as reported in a previous study ( Zhang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As predicted, db/db mice showed a higher mRNA expression of SAT1 in both the renal cortex and medulla, and also a stronger level of SAT1 expression in situ compared with db/m mice. These findings suggest a potential role of SAT1 in the development of type 2 DKD, as reported in a previous study ( Zhang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…In mammals, arginine can be catalyzed to polyamines, including putrescine, spermidine, and spermine. There is growing evidence suggesting that the dysregulation of polyamine metabolism can cause changes in high glucose-induced energy perturbation, including streptozotocin (STZ)-induced diabetic cardiomyopathy ( Wang et al, 2020a ), type 1 DKD ( Zhang et al, 2021 ), and retinopathy ( Liu et al, 2020 ), thus making it a promising target for therapeutic intervention. It has been reported that, as ROS scavengers, spermine and spermidine can protect DNA from free radical attacks, regulating cell proliferation, differentiation, and apoptosis ( Pegg, 2009 ; Wang et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the reduction in p-AMPK level and the resulting increase in p-mTOR level in HG group did not lead to the inhibition of autophagy, indicating that the high-glucose condition suppressed the activation of AMPK, and the AMPK/mTOR axis was not the critical regulator of autophagy in high-glucose environment without other interventions. Indeed, numerous studies found that high-glucose condition enhanced autophagy while reducing p-AMPK and increasing p-mTOR [ 42 , 52 55 ]. In this study, the addition of GW501516 greatly enhanced p-AMPK level, yielding decreased mTOR level, which further increased autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental mice showed hyperglycemia, hyperinsulinemia, weight loss, and abnormal cardiac function and structure (data not shown). Spermine (SPM) is one of the important products of polyamine metabolism in mammals, which has been proven to have many myocardial protective effects, for example, antifibrosis, inhibition of oxidative stress and endoplasmic reticulum stress, promotion of autophagy, and recovery of energy metabolism (9)(10)(11)(22)(23)(24). However, the effects of immune response and related signal transduction process on the DCM model of C57BL/6J mice, and the regulatory role of SPM, a potential modulator for myocardial injury in DCM, are not clear.…”
Section: Discussionmentioning
confidence: 99%